A Boolean Analysis Predicting Industry Change: Innovation, Imitation & Business Models: The Winning Hybrid - A case study of isomorphosm in the airline industry - Kristian Anders Hvass (Copenhagen Business School (CBS), 2008)
The deregulated scheduled passenger airline industry is in a constant state of motion as managers continually adapt their business models to meet the challenging market environment. Such adaptation has led to a variety of airlines populating the industry; from the birth of low-cost carriers to the transformation of state-owned behemoths to lean and successful carriers. These dynamics challenge airline managers to continuously acclimate their business models and to understand industry evolution. This doctoral dissertation addresses the issue of industry evolution and attempts to propose future airline business models based on airline behavior. The intention is to improve understanding of industry evolution, propose a method for constructing future business models, and aid airline management in future strategic decisions. Three central themes are raised in the research: business model heterogeneity and its impact on airline performance, innovation and imitation as a justification for business model heterogeneity, and future business models grounded on airline innovation and imitation. Each theme forms the basis for the project's three analyses. The research is categorized according to the customary industrial segmentation of full-service carriers, low-cost carriers, and regional carriers. The findings show that business model heterogeneity is evident at varying degrees in the industry, and that there is a positive relationship between the level adherence to a strategic group's traditional business model and financial performance. This indicates that airlines that abide by their strategic group's traditional business model perform better than those that differentiate themselves form the traditional business model. The low-cost carrier group is the most heterogeneous while the full-service carrier group is the most homogenous, which one may attribute to the historical emergence of these two groups. Results from a global survey distributed to airline CEOs show that business model differentiation is predicated on both innovation and imitation. The research shows that all airlines innovate, however business model changes based on this phenomenon may only afford an airline an advantage for a limited time period as imitation is prolific in the industry. Airline behavior indicates that airlines that populate the periphery of their strategic group are more prone to imitate other strategic groups. In addition, it is shown that airlines that closely adhere to their strategic group's traditional business model are more likely to imitate airlines populating their own strategic group. The final analysis is based on the presence of innovation and imitation in the industry and incorporates these concepts in algebraic analyses which determine the unique combinations that continuously lead to a positive operating margin. The business model results suggest that the clear, historical distinctions between the strategic groups in the industry are becoming blurred, and that a winning hybrid may emerge.
hdl:10398/6843
Keywords: 650